Experimental studies on emission reduction in a DI diesel engine by using a nano catalyst coated catalytic converter. Issue 1 (31st December 2022) - Senthil Kumar, J.; Ramesh Bapu, B. R.; Sivasaravanan, S.; Prabhu, M.; Muthu Kumar, S.; Abubacker, M. A.
Abstract : Increased vehicle emission is one of the most important issues that have drawn the attention of policy-makers and environmentalists these days. The increasing numbers of automobiles plying on roads today in our country is causing a serious threat to the ecology through harmful pollutants and also the low cost of the fuel has encouraged people to go for diesel vehicles. Several research has been made in the field of pollution control from automobiles and research is still continuing. In this present investigation an attempt has been made to study the comparison of performance and emission characteristics of the DI diesel engine by using a barium oxide and magnesium oxide nano catalyst coated catalytic converter using wintergreen biodiesel and cerium oxide nano additives (CeO2 ) in 20 nm size blended with diesel for reducing the pollutants from the four-stroke DI diesel engine.